Biochemical and trace minerals profile in fertile and infertile postpartum Surti buffaloes - SHAH, R G; DHAMI, A J; PATEL, K P; PATIL, N V; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
Blood biochemical and trace minerals profile of 26 suckled postpartum Surti buffaloes (18 fertile,8 infertile by day 90 pp) was studied at weekly intervals from the day of calving to at least 91 dayspostpartum and the findings were correlated to reproductive status. The levels of total protein andtotal cholesterol did not differ significantly between fertile and infertile buffaloes at postpartum stages.Only cholesterol increased significantly from the day of calving (109.86±15.46 Vs 125.76±8.14 mg%)to 4-6 weeks postpartum (199.97±13.63 Vs 207.62±20.13 mg%) in both the groups. The weekly profileof all macro minerals was higher in fertile than in infertile groups throughout the post-partum periodstudied with significant differences in the levels of calcium (total and ionized) and Ca:P ratio, whichwere significantly higher in fertile than the infertile group from 1st to 6th weeks postpartum, but notthe inorganic phosphorus, and none of them differed significantly between different weeks postpartum.Plasma iron levels were highest on the day of calving in both the groups, which declinedsignificantly by 1-2 weeks postpartum and again, rose to significant level by 11-12 weeks postpartumin fertile group. Zinc, copper and manganese levels did not show any specific trend or difference atany stage postpartum in either of the groups, and the values were higher at most intervals in fertilegroup as compared to infertile group, except copper, which was significantly higher in fertile thaninfertile group at 7-8 weeks post-partum. Moreover, none of the constituents showed significantvariation between different days (0,7,14 & 21) of estrous cycle. The cholesterol had significant negativeassociations with total proteins, inorganic phosphorus and manganese. Total protein had positiverelation with zinc and copper and negative relation with ionized calcium. Iron was positively correlatedwith zinc and copper had negative correlation with manganese.
Keywords: Biochemical profile; macro-micro minerals; postpartum period; Surti buffalo